Tax treaty arbitration - Lang, Michael, 1965-; Owens, Jeffrey; Pistone, Pasquale; Rust, Alexander; Schuch, Josef; Staringer, Claus; Storck, Alfred, 1949-; Buriak, Svitlana; Lan, Shimeng; Miladinovic, Alexandra; West, Jean-Philippe Van (European and international tax law and policy series, 2020)
This book provides an overview of the effectiveness of tax treaty arbitration and the approach towards recent legislative changes in 36 countries across the globe.